Students' Perspectives on the Use of Powtoon Learning Media in Learning Nahwu - Muhammad kafahulloh; Mohamad Zaka Al Farisi (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
Mastery of nahwu knowledge is the key to achieving proficiency and accuracy in language. Like a key that opens a door, nahwu opens the way for students to understand sentence structure, word functions, and meanings contained in Arabic. This study aims to evaluate students' responses to the use of Powtoon learning media in Nahwu learning at Darul Falah Islamic Boarding School. This study uses a qualitative descriptive method with the subject of the study, namely class VIII tsanawiyah students at the Darul Falah Islamic Boarding School as many as 30 students with instruments in the form of questionnaires. The results showed that the majority of students, namely 75%, responded to the use of Powtoon with a very high level of satisfaction. They saw that this media was effective in increasing their understanding of Nahwu concepts, with a percentage of 77.47% stating so. Furthermore, around 75.87% of students also felt that Powtoon was relevant to the learning material they were learning, while 72% admitted that the use of Powtoon was able to increase their interest in learning Nahwu. In addition to these benefits, Powtoon has also been shown to contribute to an increase in students' confidence in learning Nahwu, with 71.73% of students feeling the increase. The findings of this study show that Powtoon has great potential as an interesting and effective alternative learning medium for Nahwu subjects, especially in the pesantren education environment. Thus, the implementation of Powtoon can not only enrich the student learning experience but also support better learning goals in the context of the Nahwu curriculum.